2013
DOI: 10.1007/s13199-013-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of phosphate-solubilizing peanut (Arachis hypogaea L.) associated bacteria and mechanisms involved in this ability

Abstract: In this study, attempts were made to analyze mechanisms involved in the bacterial phosphate-solubilizing ability of peanut isolates. Bacteria were taxonomically identified by analysis of 16S rDNA sequence. Levels of soluble P released by the isolates in unbuffered or buffered with Tris-HCl or MES NBRIP-BPB medium as well as the production of Dgluconic acid were determined in their culture. Presence of two of the genes encoding the cofactor PQQ of GDH enzyme was analyzed in the genome of this bacterial collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 47 publications
(83 reference statements)
11
25
0
2
Order By: Relevance
“…in current study. Our results are in line with the previous studies which reported that these organic acids play a vital role in lowering the pH of the growth medium and solubilization of phosphates (Malboobi et al 2009;Andreeva et al 2011;Castagno et al 2011;Anzuay et al 2013;Tahir et al 2013). Both these strains lowered the pH of the medium and solubilized maximum amount of P (311 AE 4 by Pantoea WP-5 and 298 AE 5 by Pseudomonas NN-4) on glucose-supplemented medium.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…in current study. Our results are in line with the previous studies which reported that these organic acids play a vital role in lowering the pH of the growth medium and solubilization of phosphates (Malboobi et al 2009;Andreeva et al 2011;Castagno et al 2011;Anzuay et al 2013;Tahir et al 2013). Both these strains lowered the pH of the medium and solubilized maximum amount of P (311 AE 4 by Pantoea WP-5 and 298 AE 5 by Pseudomonas NN-4) on glucose-supplemented medium.…”
Section: Discussionsupporting
confidence: 94%
“…This may be due to the reason that in DataBank (NCBI) the nucleotide sequences of pqqE gene are only available for Pseudomonas and Bacillus in BLAST search and the tested strains might have acquired this gene through horizontal gene transfer at some point of their phylogenetic history. The amplification and sequencing of pqqE gene in the phosphate-solubilizing strains of Pantoea and Pseudomonas has been reported previously (Andreeva et al 2011;Anzuay et al 2013;Kremmydas et al 2013). Our results confirmed the indirect role of pqqE gene in inorganic phosphate solubilization and this has been reported in previous studies (Ben Farhat et al 2009;Holscher et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Direct promotion of plant growth occurs through providing the plant with a useful compound synthesised by the bacteria, or facilitating plant uptake of specific nutrients from the environment. Pseudomonas species produce siderophores (Mavrodi et al 2001) and participate in phosphate solubilisation (Anzuay et al 2013), thereby making soil iron and phosphorus accessible to the plant. Fluorescent pseudomonads also produce the phytohormone indole-3-acetic acid (IAA; Patten & Glick 2002) and 1-aminocyclopropane-1-carboxylate (ACC) deaminase, which sequesters the ethylene precursor (Van Loon 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The isolated Bacillus sp. (JRP 39) showed the highest phosphorus solubilization capacity compared to the other strains tested (Table 3), as it is known that this genus can solubilize tricalcium phosphate 19 . Our results suggest the possibility of using this bacterium as a plant growth promoter in arid and semiarid regions, as it increases the availability of inorganic phosphorus in the soil.…”
mentioning
confidence: 92%